HEAD TEACHERS' SUPERVISION OF PROFESSIONAL DEVELOPMENT AND ACADEMIC PERFORMANCE IN EMBU AND MURANGA COUNTIES, KENYA - Muthoni, Muchiri Jane; Gitumu, Margaret Wanjiru; Mwaruvie, John (International Journal of Educational Best Practices, 2020)
Supervision means overall duties performed by a head teacher which ensures teachers perform their expected roles in the transmission of knowledge and enhance academic performances. Academic performance in examinations has consistently declined in primary schools in Kenya and the world over. The objective of the study was to; assess the relationship between the head teacher‟s supervision of professional development and academic performance in Embu and Muranga counties, Kenya. The study adopted the Role theory championed by Biddle. A descriptive survey research design was used. The Target Population was 14786 and comprised of head teachers and teachers. The researchers purposefully sampled 378 public and private primary schools. Simple random sampling was used to select 256 respondents. Data were collected using questionnaires, interviews, and observation. Reliability was ascertained by a pilot study which generated a Cronbach‟s alpha coefficient of 0.93. Data were analysed using descriptive and inferential statistics, precisely, correlation computations. The findings of the study informed that the highest percentage of supervision 87.4percentwas the head teachers‟ permission for teachers to attend seminars, workshops, and conferences. The least facilitated activity was the training of teachers by subject panels 60.3 percent. There was a negative correlation between head teachers' supervision and teacher professional development in public and private primary schools, at r=-.069<0 and P=0.602>0.05. The relationship was not statistically significant. The Supervision of teacher's professional development was not strongly linked to academic performance. There should be a balance between the supervision of teacher professional.